2013
DOI: 10.1186/1471-2369-14-201
|View full text |Cite
|
Sign up to set email alerts
|

Difference in blood pressure response to ACE-Inhibitor monotherapy between black and white adults with arterial hypertension: a meta-analysis of 13 clinical trials

Abstract: BackgroundAmong African-Americans adults, arterial hypertension is both more prevalent and associated with more complications than among white adults. Hypertension is also epidemic among black adults in sub-Saharan Africa. The treatment of hypertension among black adults may be complicated by lesser response to certain classes of anti-hypertensive agents.MethodsWe systematically searched literature for clinical trials of ACE-inhibitors among hypertensive adults comparing blood pressure response between whites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 38 publications
(39 reference statements)
3
45
0
4
Order By: Relevance
“…ACEIs were associated with a higher risk of primary outcome (myocardial infarction, stroke, and heart failure) compared with CCB (4,506 matched pairs; HR 1.45, 95% CI 1.19–1.77; P = 0.0003), and a higher risk for primary outcome was observed when ACEIs were compared with thiazide diuretics in AAs (5,337 matched pairs; HR 1.65, 95% CI 1.33–2.05; P < 0.0001) 90 . A meta-analysis of 13 different trials in the USA and Europe showed that SBP and diastolic BP reduction with ACEI monotherapy was consistently lower among AAs than among whites 91 . Therefore, as recommended by the members appointed to the Eighth Joint National Committee (JNC 8), initial anti-hypertensive therapy for the AA population should include a thiazide or CCB.…”
Section: Predictors Of Renin-angiotensin-aldosterone System Blockade mentioning
confidence: 99%
“…ACEIs were associated with a higher risk of primary outcome (myocardial infarction, stroke, and heart failure) compared with CCB (4,506 matched pairs; HR 1.45, 95% CI 1.19–1.77; P = 0.0003), and a higher risk for primary outcome was observed when ACEIs were compared with thiazide diuretics in AAs (5,337 matched pairs; HR 1.65, 95% CI 1.33–2.05; P < 0.0001) 90 . A meta-analysis of 13 different trials in the USA and Europe showed that SBP and diastolic BP reduction with ACEI monotherapy was consistently lower among AAs than among whites 91 . Therefore, as recommended by the members appointed to the Eighth Joint National Committee (JNC 8), initial anti-hypertensive therapy for the AA population should include a thiazide or CCB.…”
Section: Predictors Of Renin-angiotensin-aldosterone System Blockade mentioning
confidence: 99%
“…18 These FIGURE 3. Random-effect meta-analysis of the effects of renin-angiotensin system (RAS) inhibitors vs b-blockers on all-cause mortality, myocardial infarction, stroke, heart failure, and composite outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis on the efficacy of antihypertensive monotherapy in diabetes patients of African ancestry (20) shows that: beta blockers provide minimal reduction in systolic blood pressure, and difference from placebo is uncertain calcium channel blockers and thiazides both effectively lower blood pressure ACE inhibitors have little effect on diastolic blood pressure, but appear to reduce the risk of renal injury ACE inhibitors reduced blood pressure to a lesser extent in persons of African ancestry than in Caucasians -the average difference was 4.6 mm Hg in systolic and 2.8 mm Hg in diastolic pressure (21). ACE inhibitors should therefore not be the first-line drugs in cases of uncomplicated, mild or moderate hypertension in this group (21,24).…”
Section: Antihypertensivesmentioning
confidence: 99%
“…ACE inhibitors should therefore not be the first-line drugs in cases of uncomplicated, mild or moderate hypertension in this group (21,24).…”
Section: Antihypertensivesmentioning
confidence: 99%